Perkembangan Desa Tebas Sungai Kecamatan Tebas Kabupaten Sambas Tahun 1938-2024 - Tomi Tomi (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2025)
Tebas Sungai Village is one of the villages in Tebas District, which has a very unique history and has experienced development from its formation until now, and is the oldest village, especially in Tebas District, with a large population and a high level of education. This research aims to explore the events behind the formation of Tebas Sungai Village, find out the development of Tebas Sungai Village from 1938-2024.This type of research is qualitative research using critical analysis. The approaches used are historical, sociological and anthropological approaches. Meanwhile, data sources were obtained from primary and secondary sources. The data that has been collected is processed and analyzed through the stages of historical research methods, namely the heuristic, verification, interpretation and historiography stages. Data collection techniques in this research include observation, interviews, and documentation.The research results show that The development of Tebas Sungai Village from the colonial period, the beginning of independence, the old order to the new order to reform, until the expansion of Sambas Regency, experienced many significant changes and developments, especially in infrastructure, development and community welfare.